Evidence for glutamine synthetase function in mouse spinal cord oligodendrocytes. Issue 12 (15th August 2021) - Ben Haim, Lucile; Schirmer, Lucas; Zulji, Amel; Sabeur, Khalida; Tiret, Brice; Ribon, Matthieu; Chang, Sandra; Lamers, Wouter H.; Boillée, Séverine; Chaumeil, Myriam M.; Rowitch, David H.
Abstract: Glutamine synthetase (GS) is a key enzyme that metabolizes glutamate into glutamine. While GS is highly enriched in astrocytes, expression in other glial lineages has been noted. Using a combination of reporter mice and cell type‐specific markers, we show that GS is expressed in myelinating oligodendrocytes (OL) but not oligodendrocyte progenitor cells of the mouse and human ventral spinal cord. To investigate the role of GS in mature OL, we used a conditional knockout (cKO) approach to selectively delete GS‐encoding gene ( Glul ) in OL, which caused a significant decrease in glutamine levels on mouse spinal cord extracts. GS cKO mice ( CNP‐cre + :Glul fl/fl ) showed no differences in motor neuron numbers, size or axon density; OL differentiation and myelination in the ventral spinal cord was normal up to 6 months of age. Interestingly, GS cKO mice showed a transient and specific decrease in peak force while locomotion and motor coordination remained unaffected. Last, GS expression in OL was increased in chronic pathological conditions in both mouse and humans. We found a disease‐stage dependent increase of OL expressing GS in the ventral spinal cord of SOD1(G93A) mouse model of amyotrophic lateral sclerosis. Moreover, we showed that GLUL transcripts levels were increased in OL in leukocortical tissue from multiple sclerosis but not control patients. These findings provide evidence towards OL‐encoded GS function in spinal cord sensorimotor axis, which is dysregulated in chronic neurological diseases. Main Points: Glutamine synthetase (GS) is expressed in oligodendrocytes (OL) of the mouse and human spinal cord. OL‐specific loss of function causes transient decrease in peak force. GS expression in OL is altered in chronic pathological conditions.